Spatial Planning and Community Involvement of Ecovillage Settlements in Tibang Village, Banda Aceh City - Fahrizal, Fahrizal; Yuliastuti, Nany (Universitas Negeri Semarang, 2019)
One of the handling strategies towards achieving the SDG Agenda is the 11th goal at the moment, namely environmentally sound development. Tibang, as a residential area in the city of Banda Aceh, has implemented a program from the city government that leads to environmentally sound settlements by applying the eco-village concept. This step has received support from the government in the form of policies and the existence of community institutions that care about the environment but have not been implemented optimally. Based on the problem in this study, how is the assessment of residential and residential areas in Tibang Village an embodiment of environmentally friendly villages? This study aims to assess the factors that influence housing and settlement areas in realizing the concept of the eco-village in Tibang Village. The method used is descriptive quantitative method with factor analysis, which has 82 respondents. By analyzing using the method of assessment and weighting analysis, the results obtained indicate that Tibang settlements need to be improved, especially in maintaining the preservation and environmental quality that can be realized through space utilization and community involvement in environmental preservation. Recommendations addressed to the community to increase the utilization of residential space efficiently and optimize the role of community groups concerned with the environment by embracing all levels of society and participating in realizing the eco-village concept.